Trabajo de diagnóstico y mejora empresarial a Industrias Niko S.A. - Cavero Huayanay, Sergio Jose (2021)
The present research work has a purpose to improve the industrial structure of the production process of the company "Industrias Niko S.A." belonging to the plastic injection business, through evaluative tools or business diagnostic methods, the most important being the application of the Thibaut Model with participation in financial, commercial, operational and human resources areas. Allowing to obtain information to later analyze and identify the cause of the set of problems observed in the diagnosis with the help of a tree diagram, and finally, propose improvement proposals and select the best one taking into consideration variables such as benefit, risk, time, cost, etc.